Reflectivity and spectral attribute-based reservoir characterization: a case study from "MUN" onshore Niger delta field, Nigeria - J. M. Munyithya; C. N. Ehirim; T. Dagogo (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract Reservoir characterization plays a significant role in the exploration, development, and production of hydrocarbon reservoirs. The use of integrated approach in characterization improves on the accuracy, certainty, and robust interpretation of reflectivity data. The study aimed to integrate reflectivity and spectral attributes to adequately characterize hydrocarbon reservoirs in MUN onshore Niger delta field. Well log and rock physics analyses identified and delineated reservoirs, discriminated lithology, characterized fluid, and established relations between elastic and reservoir properties for field-wide interpretation of the reflectivity data. The wells were tied to the reflectivity data, and H4 seismic horizon was mapped. Subsequently, sweetness, reflectivity and spectral attributes were extracted along H4 horizon after inversion and spectral decomposition of the reflectivity data and independently interpreted. Channel-like structure with high-amplitudes, low-to-moderate acoustic impedance (I p), lambda–rho (λρ) and mu–rho (µρ) attribute values, and high-amplitude low-frequency spectral attributes (15–35 Hz), respectively, characteristics of hydrocarbon saturated channel sands were delineated. The channel reservoir sand is thick, porous with low volume of shale and low to moderate water saturation. Analysis of data further shows that reflectivity attributes provided a better description of fluid characteristics than the sweetness and spectral attributes, but are less sensitive to structure and exaggerated the shape and limits of the channel sands. However, the spectral attributes seem to be more robust than the reflectivity attributes in providing subtle structural and stratigraphic details of the reservoir as well as delineating by-passed hydrocarbons in the field.